Análise de desfechos clínicos de episódios de bacteremia por Klebsiella spp., Escherichia coli e Proteus spp. em pacientes críticos internados em hospital universitário - Meneses, Jaqueline Pilon de [UNIFESP] (2016)
Objective: To analyze mortality and clinical failure among patients with bloodstream infection caused E. coli, Klebsiella spp., Proteus spp. and to determine the cumulative fraction of response of major ß-lactams utilized against isolated strains. Methods: A retrospective cohort study was conducted with patients who had bloodstream infection caused by E. coli, Klebsiella spp. and Proteus spp. Between January, 1, 2011 and December, 31, 2013. Thirty-day mortality rate along, with secondary outcomes, such as clinical failure were evaluated. To determine the cumulative fraction response of ß -lactams we performed a Monte Carlo simulation with a 5000 patient?s model using the minimum inhibitory concentration of E. coli, Klebsiella spp. and Proteus spp. strains isolated. Results: One hundred patients were included in the study. The most prevalent site of bacteremia was the respiratory tract (48%). In total, 74 (79.6%) patients received appropriate empirical antimicrobial therapy and the majority (44, 47.3%) received double combined therapy. The main antimicrobials used for targeted therapy was the association with meropenem plus polymyxin B (69.3%). Regarding the targeted antimicrobial therapy, we observed that 66 (94.3%) patients received appropriate therapy. Thirty-day mortality rate was 17% (17 patients), those 12 patients (70,6%) had KPC. In multivariate analysis, the predictors of Thirty-day mortality were: septic shock (OR: 9.93; 95% CI: 1,21- 81.22, p <0.01) and presence of KPC (OR: 4.03; 95% CI: 1,24- 13,15, p = 0.02). The predictors of clinical failure were: prior use of antibiotics (OR 47.27, 95% CI: 6.19 to 360.75, p <0.001), presence of comorbidity (OR 16.65, 95% CI: 2.49 to 111.23 , p = 0.003), presence of CVC (OR: 9.45, 95% CI: 1.19 to 75.08, p = 0.03), respiratory site infection (OR: 7.35, 95% CI: from 1.53 to 35.18, p = 0.01), APACHE II score (OR 1.15, 95% CI: 1.03-1.27, p = 0.01) and septic shock (OR 5, 62, 95% CI: 1.25 to 25.20, p = 0.02). Monte Carlo simulation showed that the only antimicrobial drug which reached the ideal therapeutic target (FCR ?90 %) against the three bacterias analyzed was ceftazidime. The other ?- lactams had better cumulative fraction of response when dose and infusion time were increased. Conclusions: This study found that bloodstream infection caused by E. coli, Klebsiella spp. and Proteus spp., despite showing low mortality rates, had mortality rates among patients with KPC. The use of ?-lactams in high dosing and prolonged infusion achieved higher cumulative fraction of response, however, between the antimicrobials used, only ceftazidime reached an optimal pharmacodynamic against the three strains analyze